Multivariate volatility modeling of electricity futures - Luc Bauwens; Christian M. Hafner; Diane Pierret (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
We model the dynamic volatility and correlation structure of electricity futures of the European Energy Exchange index. We use a new multiplicative dynamic conditional correlation (mDCC) model to separate long-run from short-run components. We allow for smooth changes in the unconditional volatilities and correlations through a multiplicative component that we estimate nonparametrically. For the short-run dynamics, we use a GJR-GARCH model for the conditional variances and augmented DCC models for the conditional correlations. We also introduce exogenous variables to account for congestion and delivery-date effects in short-term conditional variances. We find different correlation dynamics for long and short-term contracts and the new model achieves higher forecasting performance compared to a standard DCC model.
Keywords: C32; C53; C58; 330; electricity futures; dynamic conditional correlations; forecasting; multiplicative component; Termingeschäft; Elektrizität; Volatilität; Stromtarif; ARCH-Modell; EU-Staaten